Polarisation analysing complementary metal‐oxide semiconductor image sensor in 65‐nm standard CMOS technology. Issue 9 (16th September 2013) - Wakama, N.; Okabayashi, D.; Noda, T.; Sasagawa, K.; Tokuda, T.; Kakiuchi, K.; Ohta, J.
Abstract : In the present study, the authors demonstrate a complementary metal‐oxide semiconductor (CMOS) image sensor implemented with on‐chip polarisers using 65‐nm standard CMOS technology. The polariser is composed of metal wire grids made of metal wires fabricated by the CMOS process. An extinction ratio of 18.8 dB was obtained for a single pixel with an on‐chip polariser, where the line/space widths have the finest pitch obtainable by 65‐nm technology. Electrical crosstalk between pixels is reduced by over 25% using a guard ring structure. Polarisation imaging by the sensor was also performed.